2013
DOI: 10.1091/mbc.e13-04-0186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperglycemia and aging on nuclear sirtuins and DNA damage of mouse hepatocytes

Abstract: In normal aging, nuclear sirtuin levels decline and specific histone acetylation increases. In diabetic mice, Sirt1 and Sirt6 levels increase, which may induce gluconeogenesis through the PGC-1α pathway and DNA repair of the oxidative damage caused by hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…SIRT1 is the most studied SIRT that regulates the expression of gluconeogenic and glycolytic enzymes and promotes the hepatic glucose output. These effects are mediated, at least in part, by interacting with PGC-1α and deacetylating it (Ghiraldini et al 2013). Consistently, treatment with the specific SIRT1 activator SRT1720 increases mitochondrial membrane potential and cellular ATP content in HepG2 cells, and this effect was blocked by PGC-1α knockdown (Minor et al 2011).…”
Section: Sirtuins (Sirts)mentioning
confidence: 61%
“…SIRT1 is the most studied SIRT that regulates the expression of gluconeogenic and glycolytic enzymes and promotes the hepatic glucose output. These effects are mediated, at least in part, by interacting with PGC-1α and deacetylating it (Ghiraldini et al 2013). Consistently, treatment with the specific SIRT1 activator SRT1720 increases mitochondrial membrane potential and cellular ATP content in HepG2 cells, and this effect was blocked by PGC-1α knockdown (Minor et al 2011).…”
Section: Sirtuins (Sirts)mentioning
confidence: 61%
“…However, Ren et al (17) demonstrated that SIRT6 mRNA levels in porcine brain decreased with age, which is an indicator of a possible increase in promoter methylation. By contrast, SIRT6 protein levels were found to be increased during aging in diabetic mice (18) and following exercise in young and older mice (19). There is also accumulating evidence that SIRT6 is regulated in a circadian fashion.…”
Section: Discussionmentioning
confidence: 95%
“…This study included 55 individuals (34 females and 21 males), aged 9-95 years, divided into 8 age groups with 10-year intervals, with the exception of the 1st (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and the 8th groups (80-95 years). Blood samples were collected at the Istanbul University Medico-Social Center, Turkey, with the written consent of the individuals who completed a form indicating their background regarding gender, age, inherited diseases, cancer, exposure to chemical or radioactive agents, permanent use of medicines, smoking habits and presence in the family of individuals aged >90 years.…”
Section: Methodsmentioning
confidence: 99%
“…Cancerous cell lines MCF-7, Saos-2 and A2780 specifically selected for chemo resistance showed decreased expression of SIRT7 compared to the original non resistant cell lines [36]. Hyperglycaemia caused an increased expression level of nuclear sirtuins SIRT1 and 6 in mouse hepatocytes but not of SIRT7 [37].…”
Section: Expression Pattern Of Sirt7mentioning
confidence: 93%
“…The decreased lifespan was primarily attributed to heart defects in the SIRT7 knockout mice [21]. Lower levels of SIRT7 expression levels were reported in hepatocytes of aged mice (56 wks old BALB/cAnUnib mice) as well as aged rats (24 week old) compared to their young counterparts [25,26,37]. Also in the recent study by Ryu et.…”
Section: Sirt7 In Aging and Senescencementioning
confidence: 94%